ANALYSIS ON DEVELOPMENT STATUS OF RV REDUCER USED IN INDUSTRIAL ROBOT IN CHINA - QIAO XueTao; ZHANG LiBin; YAN CunFu; WANG ChangLu; WANG WeiGong; ZHANG LiYong (Jixie qiangdu, 2019)
Precision speed reducer is one of the key parts of industrial robot. For a long time,its Core Technology has been monopolized by the several foreign developed countries,which seriously restricting the development of China robot industry.Technology development and its status of RV reducer at home and abroad were described in paper. Then,the main causes of restricting the development of our countries’ RV reducer have been detailed analyzed. Relevant documents and policies were sketched,which play an active role in promoting the RV reducer. Finally,some personal opinions and suggestions on how to improve the situation of our countries’ precision speed reducer were submitted.